Potensi lestari dan tingkat pemanfaatan ikan selar (Atule mate) yang didaratkan di Desa Kelong, Kabupaten Bintan, Indonesia - Ageng Nur Agustins Zahra; Dedy Kurniawan; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2019)
Yellowtail scad fish was an economic value fish that many fishermen in Kelong Village catch. One of fishing ground in Bintan was Merapas Waters. Fishing activities without considering fish stocks in nature will caused overfishing. The objective of this research was to determine the Maximum Sustainable Yield (MSY), rate and effort of utilization, and Total Allowed Catch (TAC) of Yellowtail Scad fish in Merapas waters landed on Kelong Village. The fishing gear that Fishermen in Kelong Village used to catch Yellowtail Scad fish was hand line. This research used survey method. Primary data from this research were catch and effort of Yellowtail Scad Fish, while secondary data obtained from fishermen interviews and related literature. Data analysis of this research used Schaefer method. The result of this research was the potential value of MSY is 2,501.37 kg/month with the optimum effort (f opt) 178 trip. The utilization rate of Yellowtail Scad fish was 38.48% and effort rate of Yellowtail Scad fish was 22.16%. Total allowed catch value of Yellowtail Scad fish was 2,001.1 kg. Overall, the catch of Yellowtail Scad Fish hasn’t reach overfishing, so the fishing effort can be more optimized.